Pendekatan Klinis Terpadu dan Holistik dalam Penatalaksanaan Gangguan Elektrolit pada Pasien Rumah Sakit - Wulidah Rizka (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Electrolytes are essential minerals that play a critical role in various physiological processes within the body, including the maintenance of fluid balance, proper neuromuscular function, and the transmission of nerve impulses. They are vital for the stability of the heart and other crucial organs. When electrolyte levels become imbalanced, as seen in conditions such as hyponatremia (low sodium), hypernatremia (high sodium), hypokalemia (low potassium), hyperkalemia (high potassium), and hypocalcemia (low calcium), serious health issues can arise. These imbalances can result from factors like malnutrition, excessive losses through the kidneys or gastrointestinal tract, hormonal disorders, and certain systemic diseases. Understanding the underlying pathophysiological mechanisms and clinical manifestations of these disturbances is essential for effective diagnosis and treatment. Healthcare providers must identify the root causes of electrolyte imbalances while assessing their severity to implement appropriate management strategies. This often involves gradually correcting electrolyte levels to mitigate the risk of life-threatening complications such as arrhythmias, cerebral edema, and neurological impairment. By fostering a comprehensive understanding of electrolyte imbalances, healthcare professionals can improve diagnostic accuracy and therapeutic effectiveness, ultimately leading to better patient outcomes. This knowledge is crucial in minimizing morbidity and mortality associated with these disruptive conditions, ensuring that individuals receive prompt and effective care to restore balance and maintain overall health.